Swimming Upstream: The Experience of Academic Mothers of Young Children - Hirakata, Pam E.; Daniluk, Judith C (Canadian Journal of Counselling and Psychotherapy, 2009)
A qualitative, phenomenological approach was used to explore the experiences of 10 tenured and untenured women from various disciplines, who were engaged in academic careers while mothering pre-teen children. Analysis of the in-depth interview data uncovered six themes common to the participants: vulnerability; isolation; compromise and inadequacy; overwhelming stress and pressure; lack of acknowledgement and structural support; and positive gains. The implications of the findings are discussed with emphasis being placed on how the academy can become more responsive to the needs of women faculty who are raising young children.